Generic Interventions in Territories with Unique Particularities. Assuming and Differentiating the Rural Condition [Intervenções Genéricas Em Territórios Com Particularidades Únicas. Assumir E Diferenciar a Condição de Ruralidade] [Intervenciones Genéricas en Territorios Con Particularidades Únicas. Asumir y Diferenciar la Condición de Ruralidad] - Muñoz-Parra, C (Pontificia Universidad Javeriana, 2017)
Rural areas show a great diversity of activities and configurations alongside a complex network of articulations among economic sectors and with urban centers. The boundary between what is considered rural and what is considered urban is increasingly blurred. Rurality is a complex system, with a varied range of rural areas (Berdegue, Jara, Modrego, Sanclemente and Schejtman, 2010). The differences in terms of habitat, economy, and access to basic services in both contexts are variables that affect their specificity as unique territories. Projected interventions for rural areas, in any field, should have a specific aim for actors with unique needs. We take the concept of habitability within the intervention framework of a current Chilean public policy, in which interventions are applied as to improve the habitability condition of vulnerable families with the same intervention guidelines in rural and urban settings. © 2017, Pontificia Universidad Javeriana. All rights reserved.